Tv-serien som vor tids roman? - Nielsen, Jakob Isak (Passage - Tidsskrift for litteratur og kritik, 2012)
Jakob Isak Nielsen: "Tv-serien som vor tids roman?" Abstract Jakob Isak Nielsen: “The TV Series as the Novel of our Time?” In recent years contemporary TV series – particularly American one-hour drama series such as The Sopranos (HBO, 1999-2007), The Wire (HBO, 2002-2008) and Mad Men (AMC, 2007-) – have often been likened to many of the canonic works within the history of the novel. This article discusses the validity of this hypothesis by highlighting a number of similarities between the two art forms before ultimately demonstrating how they differ from each other and how they are best understood as products of particular media-systemic circumstances.